2006
DOI: 10.1245/s10434-006-9095-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Fine-Needle Aspiration of Clinically Negative Lymph Nodes Versus Sentinel Node Mapping in Patients at High Risk for Axillary Metastasis

Abstract: This study suggests that in patients at increased risk for axillary metastases, the use of sonographic evaluation of the axilla in combination with fine-needle aspiration is not only clinically justified, but also cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 24 publications
5
50
0
Order By: Relevance
“…19 Similar to clinical examination, the accuracy of evaluation by ultrasound only also has been shown to be variable. Indeed, despite relying on 'suspicious' imaging features (such as a lymph node size [10 mm, the absence of a fatty hilum, a hypoechoic internal echo, a circular shape, and cortical thickening 1 ), the reported sensitivity of the evaluation of axillary lymph node status by ultrasound alone has ranged from 35% 19 to 82%, 10 whereas its specificity has ranged from 73% 10 to 97.9%. 3 For ultrasound alone, de Freitas et al 5 quoted a PPV of 92%, an NPV of 49%, and a total accuracy of 67%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Similar to clinical examination, the accuracy of evaluation by ultrasound only also has been shown to be variable. Indeed, despite relying on 'suspicious' imaging features (such as a lymph node size [10 mm, the absence of a fatty hilum, a hypoechoic internal echo, a circular shape, and cortical thickening 1 ), the reported sensitivity of the evaluation of axillary lymph node status by ultrasound alone has ranged from 35% 19 to 82%, 10 whereas its specificity has ranged from 73% 10 to 97.9%. 3 For ultrasound alone, de Freitas et al 5 quoted a PPV of 92%, an NPV of 49%, and a total accuracy of 67%.…”
Section: Discussionmentioning
confidence: 99%
“…9 To improve the accuracy of the preoperative assessment of axillary lymph nodes, others have used FNA and found it to be simple, moderately accurate, and minimally invasive, and a good triage tool for the management of patients. 1,[7][8][9][10][11][12][13]15,19 Indeed, it has been shown that combining axillary ultrasonography with FNA cytology of abnormal lymph nodes can significantly reduce the number of unnecessary sentinel lymph node procedures performed by 8% to 40%, with a concomitant reduction in healthcare costs of up to 20%. [7][8][9][10]15,19 The data from the current study confirm that FNA cytology is a useful procedure with which to detect axillary lymph node metastases from breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct visualization of the tumor cells by fine-needle aspiration and cytology or core-needle biopsy and histology confirms axillary metastatic disease and avoids the need for SLN biopsy for confirmation of axillary nodal disease before definitive axillary treatment. Axillary ultrasound to direct needle biopsy of palpable disease is widely used, and some early studies support the use of ultrasound to screen for metastases in patients at high risk for axillary disease based on primary tumor characteristics (90,91). However, the sensitivity of axillary ultrasound is not as good as that of full nodal sampling and histologic examination; thus, histologic confirmation of a negative axilla by nodal sampling is needed if the ultrasound-guided needle biopsy is negative (91).…”
Section: Figurementioning
confidence: 99%
“…3 Some investigators reported that combined use of USG and FNAC could provide a highly accurate preoperative lymph node screening. 4,5 Sousa et al reported a 100% positive predictive value on finding of cortical thickness and non hilar cortical vascular flow. 6 Verbanck et al reported a sensitivity of 92% and specificity of 95% when using criteria of round or oval hypoechoic lesions with 5mm diameter or more.…”
Section: Discussionmentioning
confidence: 99%